2017
DOI: 10.1097/pai.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PD-L1 and CD8 Activity in Idiopathic and Infectious Chronic Inflammatory Conditions

Abstract: Programmed death-ligand 1 (PD-L1) can reduce the immune response by inhibiting CD8 T cell proliferation and cytotoxic activity. We studied a series of human viral (molloscum, human papillomavirus, herpes simplex, cytomegalovirus, Epstein-Barr virus, smallpox) and bacterial infections (H pylori) for the in situ expression of PD L1, mononuclear cell infiltration, and CD8 activity and compared this to noninfectious idiopathic inflammatory conditions to better define which immune responses may be more highly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…This may underlie the PD‐L1 overexpression in these diseases, as we observed. Indeed, PD‐L1 epithelial expression has been described in a small number of IBD, 20 UC 21 and CD cases 22 . Additionally, and in line with our findings, increased PD‐L1 epithelial expression has also been described in pancreatic ductal cells of patients with type 2 autoimmune pancreatitis, a condition that is often associated with UC, and thus probably pathogenetically related 23…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This may underlie the PD‐L1 overexpression in these diseases, as we observed. Indeed, PD‐L1 epithelial expression has been described in a small number of IBD, 20 UC 21 and CD cases 22 . Additionally, and in line with our findings, increased PD‐L1 epithelial expression has also been described in pancreatic ductal cells of patients with type 2 autoimmune pancreatitis, a condition that is often associated with UC, and thus probably pathogenetically related 23…”
Section: Discussionsupporting
confidence: 89%
“…We believe that this mechanism may be responsible for the PD‐L1 overexpression that we observed in PD1i colitis and IBD cases. This is supported by experimental data showing a role for PD‐1‐mediated inhibitory signals in limiting enteric inflammation in IBD 20–22,29,31,32 . Interestingly, however, one of these studies yielded opposite results, with PD‐L1‐deficient mice showing increased susceptibility to experimental gut injury, an effect that appeared to be mediated by an altered gut microbiota 32 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is known to suppress CD8 + T‐cell activation and proliferation, and promote regulatory T‐cell responses. Mezache et al . showed that PD‐L1 is highly expressed in normal gastric mucosal biopsies and upregulated even further in H. pylori‐ infected tissue.…”
Section: Immunologymentioning
confidence: 99%
“…IL-22producing T cells have previously been implicated in the pathogenesis of H. pylori infection. 25 Shamsdin et al 26 Mezache et al 27 showed that PD-L1 is highly expressed in normal gastric mucosal biopsies and upregulated even further in H. pylori-infected tissue. The majority of PD-L1 + mononuclear cells were CD8 + , indicating that these cells play an important role in modulating the mucosal immune response.…”
Section: T Cells and Cytokinesmentioning
confidence: 99%